Therapeutic Potentials of Characterized Isolate from Column Chromatography by GC-MS and Molecular Docking of Principle Active of Prunus domestica L. (Indian Journal of Chemistry (IJC), 2024)
Chromatographic techniques aid in isolating and separating phytoconstituents from natural products, enabling the discovery of innovative compounds of pharmacological and physiological importance. The present study is focused on isolation and identification the compounds in column chromatography-derived fractions using GC-MS and its biological activities. The ethyl acetate extract was column chromatographed using gradient of ethyl acetate in petroleum ether as solvent. This yielded a red coloured fraction/band (RCF) (approximately130 mg) which was further analysed by GC-MS for the identification of the bioactive phytoconstituents. The RCF was analysed for antioxidant activity by DPPH method which showed (IC50 = 43.895 mg/ml) and antibacterial activity by agar well diffusion method against E. coli which showed the zone of inhibition of 17 mm. Stigmast-5-en-3-ol, oleate (31.77%) was identified as the major phytoconstituent and molecular docking of this major constituent was carried out to observe its interaction with heme oxygenase and DNA gyrase protein chains.